Child labor : then and now - Greene, Laura (New York : F. Watts, 1992)
Surveys the history of child labor and its abuses and examines what has been done to eliminate the exploitation of children at work.
Includes bibliographical references (p. 138-140) and index.
Keywords: Child labor -- History -- Juvenile literature -- United States; Child labor -- Government policy -- History -- Juvenile literature -- United States; Child labor -- Juvenile literature; Child labor -- History